Stability and Vulnerability of Bird Flocking Behaviour: A Mathematical Analysis - Bayu Erfianto; Intan Muchtadi-Alamsyah (HAYATI Journal of Biosciences, 2019)
Given a large number of birds in the flock, we mathematically investigate the mechanism the birds move in a collective behavior. We assume that each bird is able to know its position and velocity of other birds within a radius of communication. Thus, to be able to fly in the flock, a bird has to adjust its position and velocity according to his neighbors. For this purpose, first of all, we analyze how the connectedness of the bird interaction network affects the cohesion of the stable bird flock. We further analyze a condition when the flock is vulnerable, which is mathematically indicated by means of the presence of an articulation point in bird communication network.